Study Regarding the Simulation of the Flow of a Fluid Through Pipes Intended for the Domestic Water Network, and the Causes of Their Degradation - Beatrice Daniela TUDOR; Dumitra STERIAN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
A public water supply and sanitation system refers to the infrastructure and services needed to provide drinking water, and to collect and treat wastewater, in a community or geographic area. It has the role of ensuring access to safe drinking water and correctly managing liquid waste generated by the population and industry. The paper makes a simulation, with the help of the SolidWorks program, of the flow of liquids through the pipes, and analyses the causes of the degradation of the pipes, intended for the domestic water network.